Understanding Openness to Involvement in Sexual Health Care Research: Narratives from a Sample of Black College Women in the United States. Issue 9 (22nd November 2022) - Frederick, Helyne; Wade, Jeannette; Parker, Sharon; Wilson, Dorrian; Wiley, Brianna; Taylor, Kwani
ABSTRACT: Little is known about Black college women's openness to participating in sexual health care research. Guided by literature on Black feminism, the current study involved qualitative interviews with 39 Black Women (aged 19–25, mean age 20.7) from one historically Black university and one predominantly white university who answered questions about participating in research on the sexual health of Black women. Results from our thematic analysis found that participants were willing to participate in research when they were recruited by trusted community members, particularly Black female researchers. The women were willing to participate because they saw the value in having Black women's perspectives on sexual health research and improving Black women's lives. We found that participants believed that non-Black women researchers should receive training to increase understanding of the issues facing Black women and create safe and judgment-free spaces to engage Black Women in sexual health research. Participants wanted non-Black female and all male researchers to demonstrate a genuine interest in their lives as Black women. The findings highlight the importance of listening to the perspectives of participants and their experiences with sexual health care providers.